Factors affecting customer loyalty in the telecommunications industry in the Klang Valley, Malaysia - Wong, Foong Yee; Chew, Soo Ling; Loh, Kian Leong (Universiti Putra Malaysia Press, 2015)
A vital factor in the growth and performance of a company in the current highly competitive telecommunications industry is the development and enhancement of customer loyalty. Although several studies in the past have helped explain the influence of some significant variables for loyalty, not many studies have examined the effects of certain factors such as service quality, customer value and corporate image on the loyalty of subscribers of mobile telecommunication companies or providers. Thus, the aim of this study is to explore the critical factors of service quality, customer value, corporate image and customer satisfaction that generate customer loyalty in the mobile communication service markets in the Klang Valley, Malaysia. Furthermore, this study also attempts to validate the connection between these factors and customer loyalty. This study employed the convenience sampling method to select 100 respondents in the Klang Valley, Malaysia, who are mobile phone users. Their personal information was analysed by means of descriptive analysis, while inferential analysis was used to test the hypotheses. All the hypotheses were found to be supported by the findings of the study, which also showed that the tested variables are significantly related to each other. This illustrates that mobile service providers wanting to build and maintain a competitive edge in the mobile service market should make greater efforts to enhance the quality of their service, provide superior customer value, attain higher customer satisfaction and win customer loyalty.